Investigating the effect of relationship satisfaction on postpartum women’s health-related quality of life in Burkina Faso: a cross-sectional analysis - Simon Cousens; Veronique Filippi; Clara Calvert; Marina Daniele; Rasmané Ganaba; Paul Lokubal (BMJ Open)
Introduction The period following childbirth poses physiological, physical, social and psychological challenges to women that may affect their quality of life. Few studies in Africa have explored women’s health-related quality of life (HrQoL) and its determinants in postpartum populations, including the quality of women’s relationships with their male partners. We investigated whether relationship satisfaction was associated with better HrQoL among postpartum women in Burkina Faso, 8 months after childbirth.Methods We analysed data from 547 women from the control arm of a randomised controlled trial in Burkina Faso. The study outcome was a woman’s HrQoL, assessed using the cross-culturally validated WHOQOL-BREF tool, with response categories adapted for Burkina Faso. The exposure was relationship satisfaction measured using questions adapted from the Dyadic Adjustment Scale and Marital Assessment Test tools. We calculated the median HrQOL scores for the study sample, overall and for each domain of HrQOL (physical, psychological, social and environmental). The association between relationship satisfaction and HrQoL was examined using multiple linear regression models with robust SEs.Results Postpartum women had high median HrQoL scores in the physical (88.1), psychological (93.1), social (86.1) and environmental (74.0) domains and overall HrQoL (84.0). We found that higher relationship satisfaction is associated with increased HrQoL. After adjusting for potential confounders, we found that for each point increase in relationship satisfaction score, the increase in HrQoL was 0.39 (p<0.001) for the overall HrQoL; 0.32 (p=0.013) for the physical domain; 0.25 (p=0.037) for the psychological domain; 0.46 (p<0.001) for the social domain and 0.49 (p<0.001) for the environmental domain.Conclusion Higher relationship satisfaction is associated with higher HrQoL scores. Policies should aim to support women to cope with the challenges of childbirth and childcare in the postpartum period to improve postpartum women’s HrQoL.